Obtenção e caracterização de filmes biodegradáveis de amido de mandioca utilizando solvente eutético profundo natural - Foregatti, Anielli da Silva (2023)
Research for obtaining biodegradable plastics originating from renewable natural sources, has grown due to their potential to replace plastics from fossil sources. In this sense, the natural deep eutectic solvents, NADES, have been presented as an alternative to obtaining starch films. Thus, the aim of this work was to produce and characterize cassava starch films by partially and completely replacing glycerol, a commonly used plasticizer, with NADES. For this purpose, a NADES using choline chloride and lactic acid, 1:3 mass ratio, was obtained, then cassava starch films containing 70% by mass of starch and 30% by mass of plasticizer were prepared by the casting method. The films were prepared with different proportions in the mass percentage of NADES/Glycerol (GL) as plasticizers: 0/100 (FGL), 25/75 (F25), 50/50 (F50), 75/25 (F75), and 100/0 (FNADES). After preparing the films, these were characterized by thickness, grammage, moisture, solubility, and permeability. The casting technique for obtaining starch films containing NADES as a plasticizer proved to be appropriate, films obtained with higher NADES contents showed better results with lower values for moisture (%) and water vapor permeability but presented more brittle when compared with film containing only glycerol or F25, with a lower concentration of NADES. Therefore, it has been concluded that the NADES used may have reacted with the polymeric chains of starch (amylose and or amylopectin) provide a more closed polymeric chain or even with higher crystallinity.